Survey and multigene characterization of stolbur phytoplasmas on various plant species in Serbia - MITROVIĆ, Jelena; PAVLOVIĆ, Snežana; DUDUK, Bojan (Phytopathologia Mediterranea, 2013)
Stolbur phytoplasmas were detected in 116 out of more than 200 samples from nine plant species col- lected in 2009‒2010 in Serbia. Phytoplasmas were detected and identified by restriction fragment length polymor- phism (RFLP) analysis of polymerase chain reaction (PCR) amplified 16S rDNA. While all strains were identi- cal on the level of 16S rDNA sequences, one strain represented a unique variant of stolbur phytoplasma with a SNP producing a new Tru1I restriction site. RFLP analyses of tuf gene amplicons, using HpaII restriction enzyme, showed profiles identical to tuf type II profile in all stolbur phytoplasma strains from Serbia. Seminested PCR for amplification of the rp gene yielded aspecific amplicons with nearly half of the samples examined. However, in the 23 samples which yielded amplicons of expected size, RFLP analysis with AluI restriction enzyme showed profiles with some variations. RFLP analyses of the amplified complete secY gene, using Tru1I and AluI restriction enzymes, showed profiles indistinguishable from each other. In phylogenetic analyses of secY gene, strains belong- ing to tuf type I formed a lineage separate from the strains belonging to tuf type II. To our knowledge this is the first report of stolbur phytoplasma in valerian (Valeriana officinalis) adding a new plant species to the already wide natural host range of stolbur phytoplasma.